ANALISIS BEBERAPA FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA GURU - Purwanto, Erni Widajanti - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2006)
ABSTRACT This research executed in Sub-Province region of Boyolali. Population counted 3628 people, big sample counted 98 responder. Result of research of show that : (1) There are positive influence not significance leadership of elementary headmaster there are satisfaction of elementary schoolteacher job. t = 1,023 with significance 0,304 > a (0,05). (2) There are positive influence which significance periodicities of elementary headmaster position to satisfaction of result work elementary schoolteacher t = 3,736 with significance 0,00 < a (0,05). (3) There are negative influence not system significance of recruitment headmaster to satisfaction of elementary schoolteacher job of t - 1,776 with value of significance 0,79 > a (0,05). coefficient of Determine (R2) equal to 0,147 meaning 14,7% variable variation of dependent can be explained by independent variable in this research, while 85,3% can be explained by other variable outside accurate independent variable. Keywords: leadership, recruitment elementary headmaster, job satisfaction.